The Epistemological Differences Between a Teacher and Researcher: A personal journey illustrating second order action research - Nicholl, Bill (Design and Technology Education: An International Journal, 2009)
This keynote address tells the personal journey of a former teacher who is now involved in educational research. Educational research is topical at the moment in Design and Technology (D&T) Education, as many initial teacher training (ITE) courses make the transition to masters level accreditation, something endorsed by the teacher training and development agency (TDA) as a means of enhancing the status of the teaching profession. The implication being that ITE courses will develop a significant research component to their courses. This paper argues against relying on experience only, or anecdotal accounts as a means for understanding or explaining the nature of the phenomena being studied. The case for conducting educational research that is ‘systematically, sceptically and ethically’ (Robson, 2002) conducted, is seen as a means understanding human behaviour, in a way that leads to conclusions that are credible (Cohen, 2007). The author draws on his experience as both a teacher in school, and as a Principal Investigator of a large, Gatsby funded research project, which looked at creativity in design and technology which is influencing policy and practice both nationally and internationally.